Identifying the main indicators to consider when choosing the most profitable property for short-term rental - Visser, Daniel (Department of Construction Economics and Management, 2023)
Short-term rental in the sharing economy has brought about a relatively inexpensive way to complement a normal household's income. In 2008 Airbnb introduced a web-based platform where anybody could advertise their “spare bedroom” for peer-to-peer lodging, and where potential guests could book and pay for this authentic stay away from home. Over the following years other web-based platforms i.e. Vrbo, Bookings.com, TripAdvisor, Google to name a few, have followed the now multi-billion-dollar Airbnb phenomenon. Income from short-term renting has the potential to outperform traditional residential longterm rent by far under certain conditions. This research investigated those factors to determine the “best buy” in this potentially lucrative market. Feng (2010) mentioned that in order to analyse a property's liquidity in the short-term rent market one should first know how much rentable traffic to expect. He further mentioned that high tourism levels and heavy buyer competition offer more liquidity, whereas limited tourism and weak competition can render a property illiquid. This means the location of the property plays the most critical role in this market. The process of finding the “best buy” in terms of short-stay rental property starts by determining the target market's needs – for example, tourists looking for cost savings, household amenities, and the potential of a more authentic local experience (Guttentag, 2015). This will determine the ideal property location. Next, property hosts need to look at the available funds to spend on the investment property in order to earn the return they are looking for. This amount will become the main filter when searching for properties in the identified locations. Finding a short-term rental property at the right price means understanding the cost of living and, importantly, the potential rentable income in the area. This involves taking into account existing rental rates, property taxes, and other indicators providing information on the cost of living in the markets being targeting. The nightly fee (price per unit per night – Rpun) becomes the next important indicator. Making sense of all the factors and role-players involved in identifying the “best buy” is difficult without a model, and therefore a decision-making model was developed. The research findings showed that the main indicators used to establish the “best buy” were the estimated value, annual net operating income, and the buyer/viewers' preference. The viewers' preference (VP) played a key role as an indicator because the property will become the owner's home while the investment value (IV) rating, derived from dividing the net operating income by the estimated value, indicates the economic prosperity of the property used in the short-term renting sector. This model was therefore called the IVVP model in this dissertation.